Circuito imobiliário e a cidade: coalizões urbanas e dinâmicas de acumulação do capital no espaço intraurbano de Belém - VENTURA NETO, Raul da Silva (Universidade Federal do Pará, 2017)
This research contributes to the discussion about the configuration of Real Estate market in Belém and recent changes which are related to the process, ongoing financialization of national Real Estate market. Context of analyzes are undertaken resulting in formation of local Real Estate market, and how intra-urban dynamics in Belém derive from this process over twentieth century. Explores mainly the context that leads to consolidating two different fronts of performance of real estate location: Central area and axis expansion highway Augusto Montenegro. In continuation, we analyze the current moment, which is marked by the entry of national Real Estate developers publicly traded in the local market, highlighting how these companies act in the urban space of the city and contrasting with the way of working of local Real Estate developers.